Pela graça da mistura : ações afirmativas, discurso e identidade negra no curso de direito em universidades públicas paraibanas - Barreto, Luciana Augusto (2014)
The state of the Brazilian Black People proves racism s aftereffect in our society, both in private scopem pronounced by prejudgment and discrimination, both on public, especially regarding public policies and the law in general. With advent of measures for inclusion in higher education favoring the black membership, mainly with Law 12.711/12, argument about rights becomes fierce for sidelines in its full citizenship and unfold races society alive in Brazil. It analyzes the implementation of affirmative action in Paraiba s public universities- Universidade Estadual da Paraíba and Universidade Federal da Paraíba- in law school, considering them as measures to promote empowerment and overcoming racism from the construction of positive black identities, as establishing new ruling relations, initially on academical environment, and reflects in all social body. From analytical Foucault, that highlights micropowers, the bloke and ruling relations, argued that shape identities of young blacks and browns are being built in law school, against of intersubjective exchanges of power between students and professors, in the assertion of their identity, and effective participation in academic life. The qualitative research involved the analysis of interviews of students and teachers of the law courses of the aforementioned universities and found, through his discourses, which are still striking the association between race and poverty, the idea of "racial democracy , formal equality and stigmatizing relationship between students / students and teachers belonging to different social classes; a significant percentage of students and teachers denies the practice of racial prejudice, although ponder their existence. It was found that the implementation of measures for inclusion in public universities of Paraíba, especially those with racial group enables the fight against racism, since it promotes diversity, and contributes, even in embryo, to form positive identities beyond of academic life.